تأثير اللغة الإندونيسية في المحادثة العربية لدى طلاب معهد المنار الحديث للتربية الإسلامية - Azwir, Azwir; Abdurrahman, Muhammad Zaky Bin (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2019)
This study discusses the influence of Indonesian on Arabic conversation of Al-Manar Islamic Boarding school students. In order to help student to be able to communicate in Arabic thus bi’ah lughawiyyah is created to train students speaking Arabic in the Islamic Boarding School environment. It is aim to fulfil the demand of global era in which Arabic is not only about learing Nahwu and Sarf but also about mastering language skills. Commmunication ability in Arabic Fusha is the most important thing that must be mastered when interacting with people from middle east countries for various need. Such as education and trade. The Islamic boarding school student often face problem in practicing Arabic expression; they are very difficult to free themselves from mother tongue. This problem is also faced by others in the world, as a result the student of the Islamic boarding school often make a mistake in their Arabic speaking expression. For example some one uses “هُناَ” to call person, meanwhile the right expression is “تَعاَل”.